Model Pengembangan Manajemen Sumber Daya Manusia UMKM Sektor Makanan dan Minuman di Era Covid-19 - Cakti Indra Gunawan; Siti Qodriyatus Solikhah; Yulita Yulita (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia experienced a decline in revenue and sales during the COVID-19 pandemic. One of the driving factors for MSME activities is human resources as the main driver. During the pandemic, the empowerment of human resources needs to be improved as a form of optimizing MSMEs. The purpose of this study is to explain how the human resource management development model can be applied to MSMEs in the food and beverage sector during the COVID-19 pandemic. This study uses a literature review method whose data sources come from secondary data and previous research studies. This research will contribute to the scientific contribution of human resource management in human resource modeling to manage MSMEs during a pandemic. The results showed that strategic innovation with the use of technology and information had a significant effect on improving employee performance and skills. The conclusion of this study shows that the use of technology and information can assist the implementation of training as a form of optimizing the development of MSME human resources during the COVID-19 pandemic.